Using mechanism design theory in negotiations to improve purchasing performance. (2018) - Schulze-Horn, Ines; Pulles, Niels; Schiele, Holger; Scheffler, Paul
The purchasing and supply management field persistently seeks new or enhanced negotiation methods to improve purchasing performance. In this regard, mechanism design theory could be applied to make negotiations more effective. By drawing on the basic premises of game theory, mechanism design theory can be used by purchasers to define negotiation rules that incentivise suppliers to reduce purchasing prices. Research on mechanism design theory still appears to be somewhat underrepresented in the 'traditional' purchasing and supply management literature. Therefore, this study provides an introduction to mechanism design theory and explores the benefits of applying it to purchasing and supply management. Additionally, this study presents a case study of 28 projects to examine how mechanism design-based negotiations can be executed and how this negotiation approach differs from conventional approaches. The research shows how mechanism design theory can extend purchasers' toolbox of negotiation methods and contribute to purchasing performance.